2021
DOI: 10.1186/s42358-021-00166-8
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell transplantation for systemic sclerosis: Brazilian experience

Abstract: Background In the past 20 years, hematopoietic stem cell transplantation (HSCT) has been investigated as treatment for systemic sclerosis (SSc). The goal of HSCT is to eradicate the autoreactive immune system, which is replaced by a new immune repertoire with long-lasting regulation and tolerance to autoantigens. Here, we describe the clinical outcomes of severe and refractory SSc patients that underwent HSCT at a single Brazilian center. Patients and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 41 publications
1
24
1
1
Order By: Relevance
“…The most clinically detectable outcome of HSC administration at 5 years post transplantation was improved skin thickness, assessed by modified Rodnan's skin score (mRSS). Of note, enhanced pulmonary function (forced vital capacity and diffusing capacity of carbon monoxide) was also observed [251]. These data are consistent with previous results from three randomized controlled trials that demonstrated the superiority of autologous HSC transplantation over the standard cyclophosphamide treatment: American Scleroderma Stem Cell versus Immune Suppression Trial (ASSIST, phase II) [252], Autologous Stem Cell Transplantation International Scleroderma Trial (ASTIS, phase III) [253], and Scleroderma: Cyclophosphamide or Transplantation (SCOT, phase II) [254].…”
Section: Skin Fibrosismentioning
confidence: 94%
See 1 more Smart Citation
“…The most clinically detectable outcome of HSC administration at 5 years post transplantation was improved skin thickness, assessed by modified Rodnan's skin score (mRSS). Of note, enhanced pulmonary function (forced vital capacity and diffusing capacity of carbon monoxide) was also observed [251]. These data are consistent with previous results from three randomized controlled trials that demonstrated the superiority of autologous HSC transplantation over the standard cyclophosphamide treatment: American Scleroderma Stem Cell versus Immune Suppression Trial (ASSIST, phase II) [252], Autologous Stem Cell Transplantation International Scleroderma Trial (ASTIS, phase III) [253], and Scleroderma: Cyclophosphamide or Transplantation (SCOT, phase II) [254].…”
Section: Skin Fibrosismentioning
confidence: 94%
“…Several clinical studies demonstrated the possible benefits of HSC and MSC (mostly SVF/ASC) therapy in SS patients (Table 1). In a recent paper, Henrique-Neto et al [251] reported the results of a longitudinal study that included 70 adult SS patients with a severe SS profile who received autologous HSCs at a mean dose of 5.63 (3.21) × 10 6 CD34 + cells/kg body weight. The most clinically detectable outcome of HSC administration at 5 years post transplantation was improved skin thickness, assessed by modified Rodnan's skin score (mRSS).…”
Section: Skin Fibrosismentioning
confidence: 99%
“…Disease progression rates varied from 11.9% at 2 years to 30.4% at 4.4 years after ASHCT. 30,31 For studies with longer follow-up, the 8-year progression rate ranged from 10.5% to 24%, 29,37 reaching 42% at 11 years. 34 These different rates are probably secondary to differences in patient selection, different criteria for progression and duration of follow-up.…”
Section: Disease Progressionmentioning
confidence: 99%
“…16,18,30 Collectively, phase I/II studies show improvement of mRSS early after AHSCT, usually more pronounced within the first year after transplantation, and tending to stabilize thereafter. 16,30,32,37 Longer follow-up studies show sustained mRSS improvement for at least 60 and 96 months, respectively. 29,37 In a post-hoc analysis of a phase I/II non-randomized study, patients who underwent AHSCT with and without graft selection were compared.…”
Section: Skin Outcomesmentioning
confidence: 99%
See 1 more Smart Citation